Laser power effects on properties of laser brazing diamond coating - Long, Weimin; Liu, Dashuang; Dong, Xian; Wu, Aiping (Surface engineering, 2020)
Effect of laser power on formation mechanism of laser brazing diamond coating has been investigated for the first time and its interface microstructure was also investigated. The BNi-2 alloy solder was utilized as braze material to fabricate brazing diamond coating on 65Mn steel substrate by using fiber laser. The laser spot was scanned at a steady speed 3 mm/s. With increase in laser power, BNi-2 alloy solder layer gradually melts and spreads fully until a laser power of 1.1 kW was reached. A further increase in laser power results in intense graphitization of the surface of the diamond grits and thermal damage. The breakage of diamond is observed when laser power is increased to 1.3 kW. Four steps are observed in laser brazing process: melting, gathering, fusing and spreading. The microstructure investigation indicates that both Cr 3 C 2 and B 4 C carbides are formed at the interface between diamond and BNi-2 alloy matrix.